Locoregional Lymph Node Metastasis from Clinically Occult Breast Cancer: Prognostic Significance of Mastectomy - Andreas Werner Nærum; Emil Villiam Holm-Rasmussen; Ilse Vejborg; Ann Søegaard Knoop; Anne-Vibeke Lænkholm; Niels Kroman; Tove Filtenborg Tvedskov (Wiley, 2024)
Background and Purpose. Occult breast cancer (OBC) is a rare condition. Due to the small number of patients in previous studies, the benefits of treatment with mastectomy are still discussed. This study aims to determine the clinicopathological characteristics, treatment, and prognosis of OBC presenting with locoregional lymph node metastasis (LNM). Materials and Methods. This study included patients registered in the national Danish Breast Cancer Group (DBCG) database between 2001 and 2015, with locoregional LNM as well as a bilateral negative mammography, ultrasonography, and physical examination of the breasts. Overall survival (OS) and invasive disease-free survival (IDFS) were compared by treatment groups, ALND + RT (axillary lymph node dissection and radiotherapy) or ALND + MAST ± RT (axillary lymph node dissection, mastectomy with or without radiotherapy). Results. In total, 56 patients were included in the study, of which 37 were treated by ALND + RT, 16 by ALND + MAST ± RT, and the remaining three patients receiving different treatments. The median follow-up for the 53 OBC patients sorted by treatment group was 12.2 years (interquartile range: 10.1 years; 15.3 years). There was no significant difference in OS or IDFS between the treatment groups, except for a subgroup of 46 (out of 53) patients without verified in situ lesions before treatment, where ALND + RT treatment showed an improved OS (log-rank p=0.05). Conclusion. Treating OBC patients with ALND and radiotherapy resulted in a similar outcome as treatment with ALND and mastectomy. This supports omission of mastectomy in favor of radiotherapy of the breast in these patients.